CONFLICTING VISIONS, COMPETING EXPECTATIONS: CONTROL AND DE-SKILLING OF EDUCATION - A PERSPECTIVE FROM ONTARIO - Majhanovich, Suzanne (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2002)
ABSTRACT. This article examines recent Ontario Government regulations that have had a far-reaching impact on the working conditions and job expectations of Ontario teachers. The article explores the restructuring initiatives in education that are associated with these regulations. It argues that although the changes have been promoted in the name of excellence and quality enhancement, in fact, they have destabilized the public school system, resulted in de-skilling of teachers, and may ultimately facilitate inroads into education by the private sector. POINTS DE VUE DISCORDANTS, ATTENTES CONTRADICTOIRES: UNE PERSPECTIVE ONTARIENNE SUR LE CONTROLE ET LA DÉQUALIFICATION DE L’ÉDUCATION RÉSUMÉ. Cet article analyse les récents règlements édictés par le gouvernement de l’Ontario qui ont eu un profond retentissement sur les conditions de travail et les perspectives d’emploi des professeurs de l’Ontario. L’article analyse les initiatives de restructuration dans l’éducation qui se rattachent à ces règlements. L’auteur affirme que même si les changements ont été préconisés au nom de l’excellence et de l’amélioration de la qualité, ils ont, en fait, déstabilisé le réseau scolaire public et entraîné la déqualification des professeurs, risquant peut-être ainsi de faciliter les incursions du secteur privé dans le secteur de l’éducation.